P(x-3) + P(x+1) = 2x^{2}-10x+16, P(x) -?

marinalebedeva5 marinalebedeva5    1   31.07.2021 09:28    0

Ответы
antoshaskoroboanton antoshaskoroboanton  30.08.2021 09:36

P(x)=x²-3x

Объяснение:

Пусть P(x)=ax²+bx+c, тогда

P(x-3)=a(x-3)²+b(x-3)+c

P(x+1)=a(x+1)²+b(x+1)+c

P(x-3)+P(x+1)=2x²-10x+16

a(x-3)²+b(x-3)+c+a(x+1)²+b(x+1)+c=2x²-10x+16

a(x²-6x+9)+bx-3b+2c+a(x²+2x+1)+bx+b=2x²-10x+16

ax²-6ax+9a+bx-3b+2c+ax²+2ax+a+bx+b=2x²-10x+16

2ax²+(-6a+b+2a+b)x+9a-3b+2c+a+b=2x²-10x+16

2ax²+(2b-4a)x+10a-2b+2c=2x²-10x+16

1) 2a=2

a=1

2) 2b-4a=-10

2b-4=-10

2b=-6

b=-3

3) 10a-2b+2c=16

10+6+2c=16

2c=0

c=0

P(x)=x²-3x

ПОКАЗАТЬ ОТВЕТЫ
артем200412прков артем200412прков  30.08.2021 09:36

Объяснение:

В приложении к ответу


P(x-3) + P(x+1) = 2-10x+16, P(x) -?
ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Алгебра